K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

11 tháng 7 2024

\(\left|x+\dfrac{1}{1\cdot3}\right|+\left|x+\dfrac{1}{3\cdot5}\right|+...+\left|x+\dfrac{1}{197\cdot199}\right|=100x\)

Số lượng số hạng là: \(\left(199-3\right):2+1=99\) (số hạng) 

TH1: \(x\ge-\dfrac{1}{197\cdot199}\)

\(=>\left(x+\dfrac{1}{1\cdot3}\right)+\left(x+\dfrac{1}{3\cdot5}\right)+...+\left(x+\dfrac{1}{197\cdot199}\right)=100x\\ =>\left(x+x+...+x\right)+\left(\dfrac{1}{1\cdot3}+\dfrac{1}{3\cdot5}+...+\dfrac{1}{197\cdot199}\right)\\ =>99x+\dfrac{1}{2}\left(\dfrac{2}{1\cdot3}+\dfrac{2}{3\cdot5}+...+\dfrac{2}{197\cdot199}\right)\\ =>100x-99x=\dfrac{1}{2}\cdot\left(1-\dfrac{1}{3}+\dfrac{1}{3}-\dfrac{1}{5}+...+\dfrac{1}{197}-\dfrac{1}{199}\right)\\ =>x=\dfrac{1}{2}\cdot\left(1-\dfrac{1}{199}\right)=\dfrac{1}{2}\cdot\dfrac{198}{199}\\ =>x=\dfrac{99}{199}\left(tm\right)\) 

TH2: \(x\le-\dfrac{1}{1\cdot3}\) 

\(=>-\left(x+\dfrac{1}{1\cdot3}\right)-\left(x+\dfrac{1}{3\cdot5}\right)-...-\left(x+\dfrac{1}{197\cdot199}\right)=100x\\ =>-\left[\left(x+x+...+x\right)+\left(\dfrac{1}{1\cdot3}+\dfrac{1}{3\cdot5}+...+\dfrac{1}{197\cdot199}\right)\right]=100x\\ =>-\left[99x+\dfrac{1}{2}\left(\dfrac{2}{1\cdot3}+\dfrac{2}{3\cdot5}+...+\dfrac{2}{197\cdot199}\right)\right]=100\\ =>-99x-\dfrac{1}{2}\left(1-\dfrac{1}{3}+\dfrac{1}{3}-\dfrac{1}{5}+...+\dfrac{1}{197}-\dfrac{1}{199}\right)=100x\\ =>100x+99x=-\dfrac{1}{2}\left(1-\dfrac{1}{199}\right)\\ =>199x=-\dfrac{1}{2}\cdot\dfrac{198}{199}\\ =>199x=-\dfrac{99}{199}\\ =>x=-\dfrac{99}{199}:199=-\dfrac{99}{39061}\left(ktm\right)\)

Vậy: `x=99/199`

11 tháng 7 2024

\(a)\left[\left(1\dfrac{2}{3}\right)^2\right]^3\\ =\left(1\dfrac{2}{3}\right)^{2\cdot3}\\ =\left(\dfrac{5}{3}\right)^6\\ b)\left(-0,18^3\right)^7\\=\left(-0,18\right)^{3\cdot7}\\ =\left(-0,18\right)^{21}\\ c)\left(\dfrac{1}{3^2}\right)^6\\ =\left[\left(\dfrac{1}{3}\right)^2\right]^6\\ =\left(\dfrac{1}{3}\right)^{2\cdot6}\\ =\left(\dfrac{1}{3}\right)^{12}\)

11 tháng 7 2024

\(A\left(x\right)=3x^2\left(4x^3-2x+\dfrac{1}{3}\right)\\ =3x^2\cdot4x^3-3x^2\cdot2x+3x^2\cdot\dfrac{1}{3}\\ =12x^5-6x^3+x^2\\ B\left(x\right)=4x^3-\dfrac{1}{5}x\left(2x^2-x+5\right)\\ =4x^3-\dfrac{1}{5}x\cdot2x^2+\dfrac{1}{5}x\cdot x-\dfrac{1}{5}x\cdot5\\ =4x^3-\dfrac{2}{5}x^3+\dfrac{1}{5}x^2-x\\ =\dfrac{18}{5}x^3+\dfrac{1}{2}x^5-x\\ C\left(x\right)=\left(x^2-x+1\right)\left(x+1\right)-x\left(x^2+3\right)-15\\ =x^3+1-x^3-3x-15\\ =\left(x^3-x^3\right)-3x+\left(1-15\right)\\ =-3x-14\\ D\left(x\right)=-15x+5x\left(x^2-7x+3\right)-x^2\left(5x-8\right)+27x^2\\ =-15x+5x^3-35x^2+15x-5x^3+8x^2+27x^2\\ =\left(-15x+15x\right)+\left(5x^3-5x^3\right)+\left(8x^2-35x^2+27x^2\right)\\ =0\)

11 tháng 7 2024

\(a)A\left(x\right)=x^7-3x^2-x^5+x^4-x^2+2x-7\\ =x^7-x^5+x^4-\left(3x^2+x^2\right)+2x-7\\ =x^7-x^5+x^4-4x^2+2x-7\\ B\left(x\right)=x-2x^2+x^4-x^5-x^7-4x^2-1\\ =-x^7-x^5+x^4-\left(2x^2+4x^2\right)+x-1\\ =-x^7-x^5+x^4-6x^2+x-1\) 

\(b)A\left(x\right)+B\left(x\right)\\ =\left(x^7-x^5+x^4-4x^2+2x-7\right)+\left(-x^7-x^5+x^4-6x^2+x-1\right)\\ =\left(x^7-x^7\right)-\left(x^5+x^5\right)+\left(x^4+x^4\right)-\left(4x^2+6x^2\right)+\left(2x+x\right)-\left(7+1\right)\\ =-x^5+2x^4-10x^2+3x-8\) 

\(A\left(x\right)-B\left(x\right)=\left(x^7-x^5+x^4-4x^2+2x-7\right)-\left(-x^7-x^5+x^4-6x^2+x-1\right)\\ =\left(x^7+x^7\right)+\left(x^5-x^5\right)+\left(x^4-x^4\right)-\left(4x^2-6x^2\right)+\left(2x-x\right)-\left(7-1\right)\\ =2x^7+2x^2+x-6\)

c) Thay x = -1  vào C(x) = A(x) + B(x) ta có:

\(C\left(x\right)=-\left(-1\right)^5+2\cdot\left(-1\right)^4-10\cdot\left(-1\right)^2+3\cdot\left(-1\right)-8\\ =-\left(-1\right)+2\cdot1-10\cdot1-3\cdot1-8\\ =1+2-10-3-8\\ =-18\)

11 tháng 7 2024

\(3^{x-1}+5\cdot3^{x-1}=162\\ =>3^{x-1}\cdot\left(1+5\right)=162\\ =>3^{x-1}\cdot6=162\\ =>3^{x-1}=162:6\\ =>3^{x-1}=27\\ =>3^{x-1}=3^3\\ =>x-1=3\\ =>x=1+3=4\)

11 tháng 7 2024

\(\dfrac{1}{2}-\dfrac{1}{3}+\dfrac{1}{23}+\dfrac{1}{6}\\ =\left(\dfrac{1}{2}-\dfrac{1}{3}\right)+\dfrac{1}{23}+\dfrac{1}{6}\\ =\dfrac{1}{6}+\dfrac{1}{23}+\dfrac{1}{6}\\ =\dfrac{2}{6}+\dfrac{1}{23}\\ =\dfrac{1}{3}+\dfrac{1}{23}\\ =\dfrac{26}{69}\)

11 tháng 7 2024

\(\left(2x-1\right)^{50}=2x-1\\ =>\left(2x-1\right)^{50}-\left(2x-1\right)=0\\ =>\left(2x-1\right)\left[\left(2x-1\right)^{49}-1\right]=0\)

TH1: 

\(2x-1\\ =>2x=1\\ =>x=\dfrac{1}{2}\)

TH2:

\(\left(2x-1\right)^{49}-1=0\\=>\left(2x-1\right)^{49}=1\\ =>\left(2x-1\right)^{49}=1^{49}\\ =>2x-1=1\\ =>2x=1+1=2\\ =>x=\dfrac{2}{2}\\ =>x=1\)

0
11 tháng 7 2024

\(B=4\cdot2^7:\left(3^{11}\cdot\dfrac{1}{9}\right)\\ =4\cdot2^7:\left(3^{11}\cdot\dfrac{1}{3^2}\right)\\ =4\cdot2^7:\dfrac{3^{11}}{3^2}\\ =4\cdot2^7:3^9\\ =\dfrac{2^2\cdot2^7}{3^9}\\ =\dfrac{2^9}{3^9}\\ =\left(\dfrac{2}{3}\right)^9\)

11 tháng 7 2024

\(A=\dfrac{4^5\cdot9^4-2\cdot6^9}{2^{10}\cdot3^8+6^8\cdot20}\\ =\dfrac{\left(2^2\right)^5\cdot\left(3^2\right)^4-2\cdot2^9\cdot3^9}{2^{10}\cdot3^8+2^8\cdot3^8\cdot20}\\ =\dfrac{2^{10}\cdot3^8-2^{10}\cdot3^9}{2^{10}\cdot3^8+2^8\cdot3^8\cdot2^2\cdot5}\\ =\dfrac{2^{10}\cdot3^8-2^{10}\cdot3^9}{2^{10}\cdot3^8+2^{10}\cdot3^8\cdot5}\\ =\dfrac{2^{10}\cdot3^8\cdot\left(1-3\right)}{2^{10}\cdot3^8\cdot\left(1+5\right)}\\ =\dfrac{-2}{6}\\ =-\dfrac{1}{3}\)